Analysis, Status Verification and Transmission of HIV/AIDS of Children of Karaganda Area (Epidemiology, Clinical Presentation, Diagnostics and Rehabilitation) - Kizatova Saule (Journal of Global Pharma Technology, 2018)
We analyzed Status Verification and Transmission of HIV / AIDS by children with AIDS from 2010-2015. In Karaganda region for the entire period, based on data from the Regional Center for Prevention and Struggle for Survival from AIDS, registered cases of HIV-infected mothers who gave birth to a total of 395 children with HIV was documented despite activities directed to reach a successful prevention of HIV transmission from the mother to child. The diagnosis of HIV-infection's in children is 30 (9.3%), 61babies, transmitted from women with HIV infection.Keywords: HIV-infection, Vertical transmission, Children, Epidemiology, Clinical presentation, Diagnostics and rehabilitation.